Influence of Ownership Structure on Company Profitability and Value In Companies - Budi Andriani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2021)
The purpose of this study was to provide empirical evidence that managerial, institutional, and public ownership affect company profitability; provide empirical evidence that managerial, institutional, and public ownership affect firm value; provide empirical evidence that managerial, institutional, and public ownership have an indirect effect on firm value; and provide empirical evidence that managerial, institutional, and public ownership have an indirect effect on firm value. This study uses secondary data from companies listed on the Indonesia Stock Exchange obtained from the Indonesian Capital Market Directory (ICMD) 2013. Samples were collected using the purposive sampling method and then analyzed using Path Analysis. The results showed that managerial ownership has a positive effect on profitability; institutional ownership has a positive effect on profitability; public ownership has a positive effect on profitability; managerial ownership has a positive direct or indirect effect on firm value; institutional ownership has a positive direct or indirect effect on firm value; public ownership has a positive direct or indirect effect on company value; profitability has a positive effect on firm value.